BRAINSTORMING, EXPLORING, SHARING, TRANSFERRING KNOWLEDGE (BEST) AS A METHOD TO DEVELOP STUDENTS’ LANGUAGE COMPETENCE - Ida Bagus Nyoman Mantra; Nengah Dwi Handayani; Ida Ayu Made Sri Widiastuti (International Journal of Applied Science and Sustainable Development (IJASSD), 2023)
Language competence is the act of using language for communication purposes. Therefore, language competence is a natural manifestation of a person's linguistic competence. The student's linguistic competence level is generally reflected in their language skills. This study used a classroom action research design with two cycles of learning activities to improve students' language competence through the BEST learning method. Data were collected through pre-test, post-test, and questionnaire. The results showed that students' language competence improved significantly from cycles 1 and 2 compared to the pre-test results. Therefore, the BEST is an effective learning method for teaching language competence. This study implies that teachers should consider using the BEST learning method to develop students' language competence.